Intralesional doxycycline and bleomycin hydrochloride in the treatment of cystic hygroma - Ashfaque Nabi; K. M. N. Ferdous; Naila Atik Khan; Nazmul Hasan; M. Kabirul Islam (SpringerOpen, 2022)
Abstract Purpose Cystic lymphangioma is a common congenital lymphatic malformation. The aim of the study was to compare the safety and efficacy of doxycycline and bleomycin in the treatment of cystic hygroma. Methods A total of 60 children with cystic hygroma were included in the study after fulfillment of inclusion and exclusion criteria from July 2016 to June 2018. They were randomly assigned to the doxycycline group (group A = 30 children) or the bleomycin group (group B = 30 children). The comparative parameters between the two groups were the reduction of size of the lesion, adverse effects of both drugs, and treatment cost between groups. All patients were followed up for 6 months. Results Median age was 10.00 months in group A and 8.50 months in group B (p=0.841) Male to female ratio was 1.76:1. There was a significant reduction in the median size of the lesion in both groups after treatment (p<0.001). 86.7% of patients had an excellent response in group A whereas 60% in group B had an excellent response (P=0.049). There was more adverse effect in group B than group A (63.3% vs 36.7%, P=0.04). Conclusion Doxycycline monotherapy had a higher rate of excellent clinical outcomes with fewer side effects than bleomycin and was more cost-effective.